The Efforts of Guidance and Counseling Teachers in Minimizing Mental Health Disorders Among Gen-Z in Schools: Upaya Guru Bimbingan Konseling dalam Meminimalisir Angka Kesehatan Mental pada Gen-Z di Sekolah - Moh Saiful Bakhril Amin; Silviana Rohmah (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
BK teachers are one of the people responsible for the mental condition of every teenager per day, especially Gen-Z. where BK teachers play an active role in school to be able to condition the mental condition of each student so that they can follow learning well, so that students can know the direction of their life goals and more easily achieve their goals. Mental health rates in adolescents in Indonesia are not doing well as evidenced by the number of suicides As well as juvenile delinquency, it is a factor in the existence of mental disorders experienced by adolescents per day. Therefore, it is very important that BK teachers have a way or effort to minimize these cases. The purpose of this study is to find out how influential BK teachers are in minimizing mental health rates in adolescents in Indonesia. In this study researchers use literature review, where articles are selected using a way of reviewing or critically reviewing knowledge, Ideas, or findings contained in the body of literature obtained from online database facilities through the Google Scholar page, obtained are selected based on publications published from 2017 to 2022 (5 years). From several articles found, there is one article that states that the field of counseling guidance services that focus on mental health education is in the field of personal services, namely the need for cooperation with other partners such as health workers, and parental involvement to provide mental health information to students.